Correlation Analysis between External Factors and Students’ Physics Learning Achievement - Karyadi Karyadi; Iriwi L.S Sinon; Irfan Yusuf; Sri Wahyu Widyaningsih (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2018)
Research was conducted to determine whether there is 1) the relationship between the state of the family of learning achievement, 2) the relationship between the state schools of learning achievement, 3) the relationship between communities of learning achievement, and 4) the relationship between the state of the family, school and community environment against learning achievement. This research is associative quantitative correlational analysis techniques. The results showed: 1) There is a positive relationship between the state of the family of learning achievement, the result of the calculation shows r table> count r ie 0.51 > 0.38, 2) There is a positive relationship between the state schools of learning achievement, the result of the calculation shows r count> r table is 0.39 > 0.38, 3) There is a positive relationship between communities of learning achievement, it is shown from the results of calculations, the count r> r table is 0.51 > 0.38, and 4) There is a positive relationship between the state of the family, school and community environment on achievement study, it was shown from the calculation, the concordance coefficient 0,95 and the value of significance (p) of 0,00 <0.05.